2008
DOI: 10.2166/wst.2008.083
|View full text |Cite
|
Sign up to set email alerts
|

Design and start-up of a high rate anaerobic membrane bioreactor for the treatment of a low pH, high strength, dissolved organic waste water

Abstract: A Submerged Membrane Anaerobic Reactor (SMAR) is being developed for the treatment of waste water originating in Sasol's coal to fuel synthesis process. The laboratory-scale SMAR uses A4-size submerged flat panel ultrafiltration membranes to induce a 100% solids-liquid separation. Biogas gets extracted from the headspace above the anaerobic mixed liquor and reintroduced through a coarse bubble diffuser below the membranes. This induces a gas scour on the membranes that avoids biomass immobilization and membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 0 publications
1
25
0
Order By: Relevance
“…More importantly, anaerobic digestion can convert the organic contents in the wastewater into an usable energy source by producing biogas. Van Zyl et al(2008) reported a 2.02 kWh energy per kg COD removed, about 7 times higher than the amount required for the system operation.…”
Section: Introductionmentioning
confidence: 93%
“…More importantly, anaerobic digestion can convert the organic contents in the wastewater into an usable energy source by producing biogas. Van Zyl et al(2008) reported a 2.02 kWh energy per kg COD removed, about 7 times higher than the amount required for the system operation.…”
Section: Introductionmentioning
confidence: 93%
“…), bio waste from municipal solid waste, sludge from wastewater treatment plants, could be utilized [41]. AnMBRs can convert up to 98% of the influent COD into biogas and very small sludge production is normally observed due to the low growth yield of anaerobic micro-organisms, [42] [43]. Organic wastes rich in carbohydrates, such as bio waste and corn silage, can improve the biogas production and the proportion of CH 4 [41].…”
Section: Energy Recoverymentioning
confidence: 99%
“…sludge process: high removal efficiency and loading rate, better control over solids retention time and hydraulic retention time (HRT), and high biomass concentrations allowed in the reactor (Aquino et al 2006;Akram and Stukey 2008a;Van Zyl et al 2008;Yuan et al 2008). Grethlein H.E.…”
Section: Historical Backgroundmentioning
confidence: 99%
“…9.1a and 9.1b. Among the three, most studies of AnMBRs were conducted for the submerged configuration (Van Zyl et al 2008;Hu and Stuckey 2006;Akram and Stuckey 2008b;Bohdziewicz et al 2008;Walker et al 2009). (c) External submerged AnMBR.…”
Section: Process Configurationmentioning
confidence: 99%